The Effects of the LLP Erasmus Mobility Programme on Cultural Biases and Affective Attitudes - Szaszkó, Rita (International Dialogues on Education Journal, 2014)
A pilot empirical investigation was carried out to gain insights into what impacts the Lifelong Learning Programme (LLP) Erasmus student mobility programme had on the participants’ cultural biases, and their affective attitudes towards the target culture, in which the Erasmus study/internship took place. A further aim of this small scale study was to pilot the interview questions for a lager scale qualitative study. The six participants were selected by convenience sampling to complete a 24-open-ended-item interview schedule, which was analysed by protocol analysis. It was found that all of the Erasmus student respondents perceived that they became more open towards the world and other cultures. Next, they experienced false beliefs about the target culture to a minor extent. Furthermore, the students at the host Erasmus partner institution had certain but limited cultural information about Hungary and they mainly know about the capital. Also the participant Erasmus students gathered information about the target country and culture before commencing their studies or traineeship aboard. Finally, all of the respondents perceived that during their Erasmus programme their positive experiences abroad outnumbered the negative ones and they would be willing to return as tourists to their Erasmus target country some day. The data analysis also detected that the interview items can yield information to study Erasmus students’ cultural biases and attitudes. However, an extension of the protocol with further cultural bias related items can be beneficial.